Produção de biossurfactante e L-asparaginase utilizando larvas secas de Tenebrio molitor como biomassa inovadora para fermentação e processo extrativo líquido - Correa, Higor Túlio (2023)
Production of high-added-value bioproducts is of great interest to industry. In search of alternative sources for these products, insects have been considered as a source of biomass as they offer sustainable development with low cost and ease of production and have not been fully explored. Tenebrio molitor biomass is already used for human and animal consumption for its high protein and lipid content; this study investigates its potential as a carbon source for production of enzymes and biosurfactants. Enzyme production was nvestigated considering l-asparaginase generated using Penicillium sp. LAMAI-505 via solid state ermentation. For biosurfactant production, Tenebrio molitor biomass was evaluated as the primary biosurfactant source; submerged fermentation of Pseudomonas aeruginosa ATCC 10145 was also evaluated. The greatest yield of l-asparaginase was 2.75 U/gds, with a 48-h incubation period, an acidic pH, a rotational bioreactor, and 0.015 g/g of glycerol and 0.10 g/g of hydrolysed Tenebrio molitor as carbon sources. When used without purification and concentration, the biosurfactants produced were able to reduce the surface tension of solutions to 32.0 mN/m, achieve emulsification rates of 100%, and have detergency similar to commercial detergents (diluted at 1.0% wt/vol).